Pendampingan Pengembangan Aplikasi Etakon Desa Tegal Wangi Kabupaten Cirebon - Raditya Danar Dana; Fadhil Muhammad Bsysyar; Agus Bahtiar (CV. Multi Kreasi Media, 2023)
Tegal Wangi Village is a partner location in this service. A case that often occurs in this village is difficulty in accessing health information and education services. The Tegal Wangi Village community has long faced obstacles in obtaining relevant information regarding their health conditions, especially when it comes to questions about their health conditions. Apart from that, educational issues are also the focus of this service, with gaps in access to education affecting the understanding and knowledge of the people in this village. Based on the discussion of community service that has been described, then the conclusion with the theme